2018
DOI: 10.1177/1744259118767197
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of convective heat transfer in a ventilated rectangular cavity

Abstract: This work presents the design, construction, and evaluation of a rectangular ventilated cavity. The cavity has a heated wall, a fixed air inlet port, and an air outlet port that can change in four different configurations: C-1, the outlet gap is on the upper side of the left wall; C-2, the outlet is on left of the top wall; C-3, the outlet is in the middle of the top wall; and C-4, the outlet is on right of the top wall of the cavity. The experimental tests were carried out with a heating power of 200 and 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The fact that Configuration (II) offers the highest flow rate among three proposed configurations, as seen in Figures 5-7 and 9, agrees well with the experiments by Macias-Melo et al [27] and Vaquez-Ruiz et al [28]. They reported that for a room with a heated wall, the highest airflow rate is obtained when the opening or the roof vertical solar chimney is right on top of the heated wall.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The fact that Configuration (II) offers the highest flow rate among three proposed configurations, as seen in Figures 5-7 and 9, agrees well with the experiments by Macias-Melo et al [27] and Vaquez-Ruiz et al [28]. They reported that for a room with a heated wall, the highest airflow rate is obtained when the opening or the roof vertical solar chimney is right on top of the heated wall.…”
Section: Discussionsupporting
confidence: 88%
“…The problem of the natural ventilation of a room with a wall heated by solar radiation has also been considered in many previous studies. With a simple opening at the top of the room with one vertical wall heated, Marcias-Melo et al [27] showed that the most efficient case for removing heat was when the opening was on the top of the heated wall. To enhance the ventilation rate, Vazquez-Ruiz et al [28] added a solar chimney to the top of the room.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that increase of the exterior thermal resistance (R value) may improve cavity conditions in HI structures, but finding an optimal ventilation rate is challenging. The results of Macias-Melo et al (2018), Langmans et al (2016, Viljanen et al (2020) and Jensen et al (2020) suggest that exterior insulation may reduce the ventilation rate of cavity in summer, because it partially prevents the warming of the cavity by solar irradiation. Earlier studies aimed at improving the hygrothermal conditions in the cavities of HI walls have not been found.…”
Section: Introductionmentioning
confidence: 99%
“…Subudhi et al [33] concluded from their study that natural ventilation depends on the position and size of the openings. Xamán et al [34], Macias-Melo et al [35], Serrano-Arellano et al [36] and Xamán et al [37] too established that ventilation, and hence, thermal comfort is dependent on the position of the opening. Moosavi et al [38] did a comprehensive review of earlier studies done for different design considerations in a building to obtain an optimum and effective ventilation and suggested the outlet opening size as the most influential parameter affecting the behaviors of the ventilation pattern along with the indoor thermal condition.…”
Section: Introductionmentioning
confidence: 99%